Perjuangan membela Melayu UMNO Selangor, 1946-2006 - Chamil Wariya (Media Global Matrix, 2006)
History and development of Selangor branch of UMNO, United Malays National Organisation, 1946-2006; volume commemorating the 60th anniversary of UMNO, the ruling party in Malaysia